Transition-Metal-Free Synthesis of C‑Glycosylated Phenanthridines via K2S2O8‑Mediated Oxidative Radical Decarboxylation of Uronic Acids - Zhou, Xin; Wang, Peng; Zhang, Li; Chen, Pengwei; Ma, Mingxu; Song, Ni; Ren, Sumei; Li, Ming (Journal of organic chemistry, 2018)
We have developed an efficient protocol for the synthesis of C-glycosylated phenanthridines. Tetrafuranos-4-yl and pentapyranos-5-yl radicals, generated from K2S2O8-mediated oxidative decarboxylation of furan- and pyranuronic acids, undergo attack to 2-isocyanodiphenyls and ensuing homolytic aromatic substitution to provide diverse C-glycosylated phenanthridines in satisfactory yields without resort to transition metals. This reaction tolerates various functional groups, and enables ready synthesis of complex oligosaccharide-based phenanthridines. The C-glycosylated phenanthridine derived from β-cyclodextrin has been prepared, which might be potential in medicinal and biological chemistry due to its flexible conformation.